Perkembangan Lembaga Pendidikan Madrasah di Indonesia Pra Kemerdekaan Tahun 1908-1942 - Alfikri, Harits Harifan (Program Studi Pendidikan Sejarah Fakultas Ilmu Sosial dan Hukum Universitas Negeri Jakarta, 2024)
Abstract: This research aims to explore the development of madrasah educational institutions in Indonesia prior to independence from 1908 to 1942. The research findings indicate that the emergence of madrasah education was influenced by four factors: the desire to return to the Qur'an and Hadith, the enthusiasm of nationalism in eradicating the colonizers, the strengthening of social, economic, traditional, and state foundations, and the reform of Islamic teaching in Indonesia. The emergence and progress of madrasah teaching institutions in West Sumatra were influenced by the contributions of Islamic reformist figures in the field of education, such as Sheikh Ahmad Khatib, Abdullah Ahmad, Zainuddin Lebay El-Yunusi, and Rahmah El-Yunusiah. Meanwhile, the emergence and development of madrasah educational institutions in Central Java and East Java were driven by two major religious organizations, namely Muhammadiyah and Nahdlatul Ulama. The development of madrasahs was led by reformists, including KH. Ahmad Dahlan and KH. Hasyim Asy'ari. This research suggests the importance of developing modern and open madrasah education to strengthen Islamic education in Indonesia. Keywords : madrasah, Islamic education, renewal, Sumatra Barat, Jawa Tengah, Jawa Timur. Abstract : Penelitian ini bertujuan untuk mengeksplorasi perkembangan lembaga pendidikan madrasah di Indonesia sebelum kemerdekaan dari tahun 1908 hingga 1942. Hasil penelitian menunjukkan bahwa kemunculan pendidikan madrasah dipengaruhi oleh empat faktor, yaitu dorongan akan kembali ke Al-Quran dan Hadist, antusiasme nasionalisme membasmi penjajah, penguatan fondasi sosial, ekonomi, tradisi, dan ketatanegaraan, serta pembaharuan pengajaran Islam di Indonesia. Kemunculan dan kemajuan lembaga pengajaran madrasah di Sumatera Barat dipengaruhi oleh sumbangsih para tokoh pembaharu Islam dalam bidang pendidikan seperti Syaikh Ahmad Khatib, Abdullah Ahmad, Zainuddin Lebay El-Yunusi, dan Rahmah El-Yunusiah. Sedangkan kemunculan dan perkembangan lembaga pendidikan madrasah di Jawa Tengah dan Jawa Timur didorong oleh dua organisasi keagamaan besar, yaitu Muhammadiyah dan Nahdlatul Ulama. Pengembangan madrasah tetap dipimpin oleh para reformis, termasuk KH. Ahmad Dahlan dan KH. Hasyim Asy'ari. Penelitian ini menyarankan pentingnya mengembangkan pendidikan madrasah modern dan terbuka untuk memperkuat pendidikan Islam di Indonesia. Kata kunci : madrasah, pendidikan Islam, pembaharuan, Sumatera Barat, Jawa Tengah, Jawa Timur.